MENGUNGKAP KARAKTER KERJASAMA SISWA SEKOLAH DASAR - Ratna Sari Dewi; Sukirwan Sukirwan (Jurnal Ilmu Pendidikan Ahlussunnah, 2021)
This research is a preliminary study, aimed at obtaining factual information on character education in cooperation with elementary school students in SDN 1 Sumurbandung, Lebak Regency. Research methods use quantitative research procedures. The results of the study obtained the practice of 2013 curriculum learning through the Cooperative Learning Model in its implementation is still oriented to the ability of students' knowledge and skills of students, while the ability of attitudes, especially the character of cooperation still requires a process of improvement based on research results where students are still weak in: Helping friends in need help (58.33%), Together in doing work (51.85%). Share task equipment with others (35.19%), Invite others in activities (30.56%), Say thank you (55.56%), Concentrate seriously (74.07%), Give advice in groups (49.07%), Feel happy to be part of a group (56.48%), Carry out activities designed by the leader (49.07%). Following the leader's direction (49.77%), Following the suggestion of improving cooperation (43.52%), Able to invite others to work together (55.56), Able to direct others to work together (57.41%), Overall ability to work with students with average grades the average of 52.91% is in the sufficient category, meaning that students are only sufficient in their ability to work together